2007
DOI: 10.1111/j.1365-2443.2007.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

PAX6 and SOX2‐dependent regulation of the Sox2 enhancer N‐3 involved in embryonic visual system development

Abstract: Sox2 is universally expressed in the neural and placodal primordia in early stage embryos, and this expression depends on various phylogenetically conserved enhancers having different regional and temporal specificities. The enhancer N-3 was identified as a regulator of the Sox2 gene active in the diencephalon, optic vesicle, and after the contact of the vesicle with the ectoderm, in the lens placodal surface area, suggesting its involvement in embryonic visual system development. A 36-bp minimal essential cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 32 publications
4
79
1
4
Order By: Relevance
“…Of course, the involvement of other transcription factors in the regulation of Rax expression cannot be excluded. Furthermore, previous studies on Pax6-Sox2 cooperation have reported that differences in the sequences of cisregulatory elements result in differences in the threshold protein levels required for the cooperative action to occur (36). The present work permits us to speculate that Otx2 and Sox2 coregulate the expression patterns of multiple target genes in various subdomains of the brain and eye and that the expression levels of the different target genes are controlled by the different stoichiometric ratios of the individual subdomains.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Of course, the involvement of other transcription factors in the regulation of Rax expression cannot be excluded. Furthermore, previous studies on Pax6-Sox2 cooperation have reported that differences in the sequences of cisregulatory elements result in differences in the threshold protein levels required for the cooperative action to occur (36). The present work permits us to speculate that Otx2 and Sox2 coregulate the expression patterns of multiple target genes in various subdomains of the brain and eye and that the expression levels of the different target genes are controlled by the different stoichiometric ratios of the individual subdomains.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have reported that the distance between the Sox2-and Pax6-binding sites is conserved between two cis-regulatory elements and that insertions of a few base pairs between these sites ablate the cooperative action of Sox2 and Pax6 (11,36), which raises the possibility that, in addition to the individual sequences of the binding sites, the gap between two binding sites contributes to the stoichiometric association and the interdependence of Otx2 and Sox2. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the interaction of SOX proteins with cell specific partners is important for stable binding to DNA and target specificity (Kamachi et al 2000, Wilson & Koopman 2002. For instance, the co-operative interaction between Sox2 and Pax6 is required for the activation of the enhancer of d-crystalline during lens formation , Inoue et al 2007). On the other hand, in embryonic stem cells, the interaction of Sox2 with class III POU proteins results in the activation of the Nestin enhancer (Tanaka et al 2004).…”
Section: Sox Proteinsmentioning
confidence: 99%
“…SOX2 codifica un factor de transcripción con una función primordial en el desarrollo embrionario en numerosos tejidos, incluyendo el ojo y el cerebro. Actúa de manera cooperativa con PAX6 para regular otros genes que promueven el desarrollo del cristalino 16,18 , y se han descrito diversas mutaciones dominantes de este gen en sujetos con anoftalmia o microftalmia, incluyendo mutaciones puntuales y deleciones completas o parciales 19 . Una de las mutaciones más frecuentemente identificadas y que corresponde a una deleción de 20 bases en el extremo 5' del gen fue descrita inicialmente en pacientes mexicanos con anoftalmia [20][21][22] .…”
Section: Sox2unclassified